The Psychosocial Impact of Congenital Cytomegalovirus on Caregivers and Families: Lived Experiences and Review of the Literature - Michelle P. Zappas; Amanda Devereaux; Megan H. Pesch (MDPI AG, 2023)
Caring for a child with congenital cytomegalovirus (cCMV) can be costly for families, not only in terms of out-of-pocket expenses, but also in terms of caregiver time, relationships, career trajectories, and mental health. These additional burdens are sometimes referred to as "spillover effects". As parents of children with cCMV, we, the authors of this article, discuss the impact that cCMV has had on our families. While multiple studies have reported on the epidemiology, prevention, screening, diagnosis, and management of cCMV, there has been minimal research regarding the possible impact on the family unit. In this narrative review, we discuss the various areas of the lives of families and caregivers that may be impacted by raising a child with cCMV. Whether children are minimally or severely affected by the sequelae of cCMV, they and their families merit the progression of awareness of the virus and governmental policies to help end cCMV. As the existing cCMV-specific literature is limited, we correlate studies of other childhood disabilities and find the mutuality experienced by families affected by cCMV.